2021
DOI: 10.1093/jac/dkab208
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin susceptibility among invasive MSSA infections: a multicentre study in 16 Spanish hospitals

Abstract: Objectives To determine the prevalence of penicillin susceptibility among MSSA causing bloodstream infections (BSIs) in 16 Spanish hospitals and to characterize the penicillin-susceptible MSSA (MSSA-PENS) isolates. Methods A total of 1011 Staphylococcus aureus isolates were collected from blood cultures in 16 Spanish hospitals during 2018–19 (6–12 months) and their susceptibility to 18 antimicrobials was determined. The MSSA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Also notable is that 43 out of 114 genomes from six STs presented blaZ . For comparison, high penicillin susceptibility rate has been reported in MSSA from bloodstream infections in humans, primarily from CCs 5 and 398 46 . Penicillin may be considered a therapeutic option in the treatment of animal infections, but ST identity should be carefully considered as blaZ appears to be more phylogenetically widespread in animal-associated S. aureus .…”
Section: Discussionmentioning
confidence: 99%
“…Also notable is that 43 out of 114 genomes from six STs presented blaZ . For comparison, high penicillin susceptibility rate has been reported in MSSA from bloodstream infections in humans, primarily from CCs 5 and 398 46 . Penicillin may be considered a therapeutic option in the treatment of animal infections, but ST identity should be carefully considered as blaZ appears to be more phylogenetically widespread in animal-associated S. aureus .…”
Section: Discussionmentioning
confidence: 99%
“…CC5 is one of the most dominant clones among both MRSA and MSSA in China [ 27 ]. In addition, CC5 has also been demonstrated as one of the most prevalent clones among MSSA-PEN S strains in other studies [ 32 , 41 ].…”
Section: Discussionmentioning
confidence: 76%
“…Several additional amino acid changes were detected among these isolates (Figure S2). For instance, the mutations in isolates SKLX44218, SKLX56709 and SKLX61252 introduced a frameshift (c.92delA) introducing a premature stop codon at codon 43 (L43*); the G223 T substitution in isolate SKLX62838 resulted in a premature stop codon at codon 75 (E75*); and the nonsynonymous amino acid substitutions occurring in the other isolates comprised those previously reported in the CC5-t002 isolate X1953 [ 32 ]. We also examined the mutations in the blaI gene for these 11 isolates and found that there were no changes in the sequences of the blaI gene in isolates SKLX56709 and SKLX61252, whereas isolate SKLX62838 exhibited a change in codon 21 (p.D21G), and the other isolates showed changes in codon 2 (p.A2 T).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations